2000
DOI: 10.1038/sj.bmt.1702517
|View full text |Cite
|
Sign up to set email alerts
|

Complications after bone marrow transplantation are manifestations of systemic inflammatory response syndrome

Abstract: Summary:Bone marrow transplantation has been established as a useful treatment for various hematological disorders and is now performed widely, but the mortality rate is still high due to various complications. A clear therapeutic policy for such complications has not yet been established because of their complex nature. We investigated whether the major complications occurring after bone marrow transplantation could be classified as aspects of the systemic inflammatory response syndrome. Subjects were 10 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
73
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 15 publications
(13 reference statements)
1
73
0
4
Order By: Relevance
“…The period prior to stem-cell engraftment may involve the worst clinical condition of SCT recipients, associated with predispositions to serious infections, regimen-related toxicity and immunological stress, resulting in sepsis, and acute inflammatory response syndrome. 27 Accordingly, the incidence of AKI during this period may become a trigger of multiorgan failure, as AKI is often accompanied by a systemic excessive inflammatory response that involves the mechanisms of developing remote extra-renal organ dysfunction. 28,29 The occurrence of early AKI may be associated with a delay or failure of stem-cell engraftment, as the disease status of AKI might affect the function of Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…The period prior to stem-cell engraftment may involve the worst clinical condition of SCT recipients, associated with predispositions to serious infections, regimen-related toxicity and immunological stress, resulting in sepsis, and acute inflammatory response syndrome. 27 Accordingly, the incidence of AKI during this period may become a trigger of multiorgan failure, as AKI is often accompanied by a systemic excessive inflammatory response that involves the mechanisms of developing remote extra-renal organ dysfunction. 28,29 The occurrence of early AKI may be associated with a delay or failure of stem-cell engraftment, as the disease status of AKI might affect the function of Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Engraftment syndrome after transplantation TR Spitzer 34,35 Chang et al 9 reported increased levels of suppression of tumorigenicity, IL-2 receptor-alpha and TNF-receptor-1 levels in persons with ES similar to persons with acute GVHD. However, there is no unique or consistent pattern of cytokine abnormalities in persons with ES.…”
Section: Engraftment Syndromementioning
confidence: 99%
“…First, 'conditioning-associated tubular injury' occurred, possibly due to the administration of a high amount of cyclophosphamide, as it is known to impair the uroepithelium through its toxic metabolite, acrolein [15]. Next, the inflammatory and cytokine cascade that accompanies the infused allogeneic stem cells affected kidney function [2,16,17], as the serum proinflammatory cytokine levels were highly increased in parallel with the increasing serum Cr levels. The pathophysiologic nature of the increased CRP remained conjectural, infectious inflammation or non-infectious inflammation or both, in this case.…”
Section: Discussionmentioning
confidence: 99%